Echocardiographic assessment after surgical repair of Tetralogy of Fallot - Mario eCarminati; Francesca Romana Pluchinotta; Luciane ePiazza; Angelo eMicheletti; Diana eNegura; Massimo eChessa; Gianfranco eButera; Carmelo eArcidiacono; Antonio eSaracino; Claudio eBussadori (Frontiers Media S.A., 2015)
Surgical correction of Tetralogy of Fallot is still one of the most frequently performed intervention in pediatric cardiac surgery, and in many cases it is far from being a complete and definitive correction. It is rather an excellent palliation that solves the problem of cyanosis but predisposes the patients to medical and surgical complications during follow-up. The decision-making process regarding the treatment of late sequel are among the most discussed topics in adult congenital cardiology. In postoperative Fallot patients, echocardiography is used as the first method of diagnostic imaging and currently allows both a qualitative observation of the anatomical alterations and a detailed quantification of right ventricular volumes and function, of the right ventricular outflow tract, and of the pulmonary valve and pulmonary arteries. The literature introduced many quantitative echocardiographic criteria useful for the understanding of the pathophysiological mechanisms involving the right ventricle and those have made much more objective any decision-making processes.